About a debt - Oliveira Albano, Adriana Helena de (Univ Estadual Paulista-unesp, 2011)
This article studies the guilt in poetic memorialist of Carlos Drummond de Andrade (1974, 1979) by two poems, Justificacao, found in Menino Antigo and O viajante pedestre, found in Esquecer para Lembrar. We will use deconstruction as a theoretical apparatus proposed by Jacques Derrida to discuss the relationship between subject and writing memory and the guilt of this remembering.
Keywords: Drummond; Memories; Derrida